Teacher Strategies in Developing Early Childhood Gross Motor Skills in the New Normal Era - Azura, Alfi; Muryanti, Elise (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
This study's purpose was to describe teachers' strategies in implementing gross motor development activities in children aged 5-6. The research method is a descriptive and qualitative approach—the data collection using interview techniques, observation, and documentation. The source data was obtained from the kindergarten class teacher. The results of this study indicate that kindergarten teachers prepare a variety of strategies that can be used in the implementation of the development of gross motor skills of children. It starts from designing a learning plan, designing activities according to the theme and sub-theme of learning, preparing media based on the selected theme by utilizing items around the house, and giving talks, demonstrations, and direct practice. In this method, the teacher explains the purpose of the activity first to the child and then practices it with the child. Based on the research results, it can be concluded that teachers become more creative in preparing materials and media.   Abstrak Tujuan penelitian ini ialah untuk mendeskripsikan strategi guru dalam pelaksanaan kegiatan pengembangan motorik kasar pada anak usia 5-6 tahun. Metode penelitian ialah metode dekriptif dengan pendekatan kualitatif. Pengumpulan data menggunakan teknik wawancara, observasi, serta dokumentasi. Sumber data diperoleh dari guru kelas Taman Kanak-kanak. Hasil dari penelitian ini menunjukkan bahwa guru Taman Kanak-Kanak menyiapkan berbagai strategi yang bisa digunakan dalam pelaksanaan pengembangan keterampilan motorik kasar anak, yang dimulai dari membuat perencanaan pembelajaran, merancang kegiatan sesuai tema dan sub tema pembelajaran, menyiapkan media berdasarkan tema yang dipilih dengan memanfaatkan barang-barang di sekitar rumah, serta menggunakan metode pemberian tugas, demontrasi, dan praktek langsung. Dalam penerpan metode tersebut guru menjelaskan tujuan kegiatan terlebih dahulu kepada anak kemudian ikut mempraktikkannya bersama anak. Berdasarkan hasil hasil penelitian dapat disimpulkan bahwa guru menjadi lebih kreatif dalam menyiapkan bahan dan media.